Carbohydrate-induced hypertriacylglycerolemia: historical perspective and review of biological mechanisms - Parks, Elizabeth J; Hellerstein, Marc K (The American journal of clinical nutrition, 2000)
Current trends in health promotion emphasize the importance of reducing dietary fat intake. However, as dietary fat is reduced, the dietary carbohydrate content typically rises and the desired reduction in plasma cholesterol concentrations is frequently accompanied by an elevation of plasma triacylglycerol. We review the phenomenon of carbohydrate-induced hypertriacylglycerolemia, the health effects of which are among the most controversial and important issues in public health nutrition today. We first focus on how seminal observations made in the late 1950s and early 1960s became the basis for subsequent important research questions and areas of scientific study. The second focus of this paper is on the current knowledge of biological mechanisms that contribute to carbohydrate-induced hypertriacylglycerolemia. The clinical rationale behind mechanistic studies is this: if carbohydrate-induced hypertriacylglycerolemia shares a metabolic basis with endogenous hypertriacylglycerolemia (that observed in subjects consuming high-fat diets), then a similar atherogenic risk may be more likely than if the underlying metabolic mechanisms differ. The third focus of the paper is on both the positive metabolic changes that occur when high-carbohydrate diets are consumed and the potentially negative health effects of such diets. The review concludes with a summary of some important research questions that remain to be addressed. These issues include the level of dietary carbohydrate that induces carbohydrate-induced hypertriacylglycerolemia, whether the phenomenon is transient or can be avoided, whether de novo lipogenesis contributes to the phenomenon, and what magnitude of triacylglycerol elevation represents an increase in disease risk.